Invasion of the boy snatchers : a Clique novel - Harrison, Lisi. (New York : Little, Brown, 2005)
Following Christmas break, the girls are back together, but everything seems different with the addition of Alicia's cousin from Spain who is spending the semester at Octavian Country Day School.
Keywords: Friendship -- Fiction; Cliques (Sociology) -- Fiction; Students, Foreign -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Westchester County (N.Y.) -- Fiction